A Comparison of Policy Instruments to Reduce Greenhouse Gas Emissions1. Issue 3 (5th July 2016) - Freebairn, John
Abstract : Tax, emission trading schemes, regulations and subsidy policy instruments to reduce Australian greenhouse gas emissions are assessed. Australian recent and proposed examples are used as illustrations. Comparative pollution reduction cost, tax interaction distortion costs, redistribution effects and operating cost properties are evaluated. A tax instrument with a comprehensive base, combined with recycling the revenue windfall to households, is argued to be a suitable guideline for future policy; some regulations to counter information and other market failures can be important complements.